Mobile compact gravity-force concrete mixer - Vasyliev, Ievhen; Taranenko, Dmytro (Academic journal Industrial Machine Building Civil Engineering, 2024)
The article discusses the design of a compact gravity-force concrete mixer, which combines the advantages of gravity and forced mixers. An analysis of existing designs and the mixing processes within them was conducted. The proposed design is promising due to its high energy efficiency, reliability, and compactness. Its small size simplifies transportation, and its versatility allows it to be placed at any construction site, which increases its flexibility of use. The mixer ensures high-quality mixing of solutions and adapts to various conditions